2019
DOI: 10.1111/jre.12642
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative differences in the subgingival microbiome of the restored and unrestored teeth

Abstract: Background and Objective Metal‐based dental restorations with a subgingival outline may enhance plaque accumulation and bacterial colonization. This study aimed to investigate whether metal‐based restorations influence the composition of subgingival microbiome. Material and Methods Per subject one site with a metal‐based restoration and one contra‐lateral site without a restoration were selected on basis of radiographic bone loss ≤2 mm, restoration outline at sulcus level/subgingivally, pocket depth ≤4 mm, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Abusleme et al reported that inflammation was not associated with a distinct microbiome, whereas Camelo‐Castillo et al showed that increased inflammation was associated with more diverse microbiota and higher abundance of Desulfobulbus , Eubacterium , Filifactor , Streptococcus , Tannerella , and Treponema (Abusleme et al, 2013 ; Camelo‐Castillo et al, 2015 ). A third study, which examined the subgingival microbiome of restored and unrestored teeth, reported differences in the microbial profiles between bleeding and non‐bleeding restored sites; Prevotella and Treponema were detected in higher abundance in bleeding sites, whereas Enterococcus was associated with non‐bleeding sites (Rademacher et al, 2019 ). In accordance with our results, the implant system is not associated with the composition of the submucosal microbiome of peri‐implant sites (Sanz‐Martin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abusleme et al reported that inflammation was not associated with a distinct microbiome, whereas Camelo‐Castillo et al showed that increased inflammation was associated with more diverse microbiota and higher abundance of Desulfobulbus , Eubacterium , Filifactor , Streptococcus , Tannerella , and Treponema (Abusleme et al, 2013 ; Camelo‐Castillo et al, 2015 ). A third study, which examined the subgingival microbiome of restored and unrestored teeth, reported differences in the microbial profiles between bleeding and non‐bleeding restored sites; Prevotella and Treponema were detected in higher abundance in bleeding sites, whereas Enterococcus was associated with non‐bleeding sites (Rademacher et al, 2019 ). In accordance with our results, the implant system is not associated with the composition of the submucosal microbiome of peri‐implant sites (Sanz‐Martin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed not to brush their teeth on the morning of the sampling day and the night before. After a trained dentist scratched the supragingival debris with sterilized cotton balls, a subgingival plaque was collected with 40# sterilized paper points (Gapadent, Tianjin, China) that were gently inserted into the deep periodontal pocket for 20 s. Once removed from the periodontal pocket, the paper point was placed into a 1-mL sterile cryopreservation tube ( 50 ). No sample was collected if a patient had no teeth or dental implants.…”
Section: Methodsmentioning
confidence: 99%
“…This has resulted in a shift of focus away from single species to considering that increasing understanding of human health and disease requires the characterization of the microbial community. Dewhirst et al (2010); Jenkinson (2011), and Verma et al (2018) Microbial communities and their ecology have been described in several oral habitats such as teeth (Becker et al, 2002;Rademacher et al, 2019), tongue (Jiang et al, 2012;Wilbert et al, 2020), gingival sulcus (Paster et al, 2001;Wei et al, 2020), and saliva (Sakamoto et al, 2000;Nasidze et al, 2009), but with a particular focus on disease-state (Aas et al, 2005;Zaura et al, 2009) and, unfortunately, often lacking sufficient depth and spatial or temporal sampling breadth to unravel the ecology and dynamics of microbial communities (Yang et al, 2016). Moreover, less information is available regarding the healthy microbiome of the human oropharynx.…”
Section: Introductionmentioning
confidence: 99%